When Speech Becomes Crime: Defamation and Constitutional Power After Decision 78/2023 - Syaifuddin, Imam; Syahrin, Alvi; Marlina, Marlina (Universitas Negeri Gorontalo, 2025)
This study examines the constitutional and legal dimensions of defamation in Indonesia in light of Constitutional Court Decision No. 78/PUU-XXI/2023 and District Court Decision No. 8/Pid.B/2024/PN Wns. Using a normative juridical method combined with a qualitative case approach, it analyzes how the Constitutional Court’s interpretation of Article 310(1) of the Indonesian Penal Code (KUHP) as a verbal act reshapes the legal framework of defamation. Relevant regulations include Articles 310–321 of the KUHP, Articles 433–439 of Law No. 1 of 2023 (New Penal Code), and Law No. 1 of 2024 (ITE Law). The findings reveal a constitutional enforcement gap: while the Constitutional Court provides a clear interpretive standard, the Watansoppeng District Court failed to apply it despite issuing a substantively appropriate sentence. This inconsistency reflects institutional weaknesses in implementing constitutional decisions within ordinary courts. To deepen the analysis, this study draws on comparative experiences from Germany and Colombia. Both jurisdictions face similar enforcement gaps but address them through structured mechanisms, such as mandatory appellate references in Germany and the tutela mechanism in Colombia. These insights show that binding constitutional authority requires institutional enforcement measures to ensure effectiveness. The novelty of this study lies in identifying this enforcement gap as a critical challenge to constitutional supremacy in criminal defamation and situating it within a comparative perspective. It contributes to legal scholarship and judicial reform discourse by emphasizing the need for systematic judicial compliance to guarantee legal certainty, protect fundamental rights, and maintain coherence in defamation law.